Simple and Easily Applicable Method for Reducing Freshwater Consumption in Dyeing of Wool Fabric - Omaima Allam; Nagla Elshemy; Hosam El-Sayed (Journal of Natural Fibers, 2022)
Textile wet processing is one of the most water-consuming industries. The deficiency of soft water in some parts of the world urged the researchers to exert effort toward minimization of water consumption during textile wet processes. In this work, we bleach wool fabrics by hydrogen peroxide, followed by utilization of the discharged bleaching bath (DBB) in dyeing of wool with acid, reactive, and basic dyes. The residual H2O2 in the bleaching bath was decomposed into water and oxygen by adding low concentrations of potassium iodide (KI). Results of this investigation clarify that treatment of the DBB with KI is mandatory to make the bath appropriate for wool dyeing. The dyeability of wool toward the said dyes in KI-treated DBB is significantly higher than that upon dyeing with tap water. The fastness properties of the dyed fabric to washing, perspiration, and light were assessed. The turbidity, pH, total dissolved salts (TDS), total suspended salts (TSS), biological oxygen demand (BOD), and chemical oxygen demand (COD) of the bleaching effluent were assessed. Solubility of bleached/dyed wool fabrics in alkali and urea-bisulfite solutions assures the modification of some disulfide bonds along wool keratin macromolecules into cystine oxides/cysteic acid residues, and consequently the dyeability was enhanced.